Особливості пейзажної лірики Яра Славутича (на матеріалі циклу «Херсонські сонети») - Ляшенко (Накашидзе), Ірина Сергіївна (Уманський державний педагогічний інститут імені Павла Тичини, 2024)
UKR: У статті досліджуються особливості пейзажної лірики Яра Славутича у циклі «Херсонські сонети». Виявлено, що основним образом циклу є степ як ознака малої батьківщини ліричного героя. Вимальовується опозиція чужина – батьківщина, що є одним із провідних мотивів лірики Яра Славутича. У сонетному циклі чітко виокреслюються всі пори року, на що вказують рослинні та тваринні образи. Серед найбільш уживаних тропів поета при змалюванні пейзажу – метафора, епітети, персоніфікація, літота.

ENG: This paper focuses on the peculiarities of landscape poetry by Yar Slavutych in the cycle "Kherson Sonnets". It is revealed that the main image of the cycle is the steppe as a sign of the lyrical hero's small motherland. In describing the steppe, Yar Slavutych achieves high expressiveness, artistic and emotional content through a whole system of key words-images, word-concepts that create a wonderful picture of the author's worldview and feelings. These words perform an important textual function, creating a major tone of the narrative. Thanks to them, images of Ukraine, the native land, and the boundless expanse of the steppe are created. The poet was able to psychologically convey his love for his native land, his native Kherson region. The cycle "Kherson Sonnets" closes with the image of the lyrical hero's journey into the unknown future. The opposition between a foreign country and motherland emerges, and this is one of the leading motifs of Yar Slavutych's lyrics. The time in the cycle "Kherson Sonnets" is not clear. The seasons are clearly distinguished: spring - summer - autumn. In most of Yar Slavutych's sonnets from the cycle "Kherson Sonnets", attention is focused on one moment in the nature of the southern steppe, as if in a "freeze-frame". In the sonnet cycle, we meet the rich world of flora and fauna, which the poet personifies in his depiction. An important place in the image system of the cycle "Kherson Sonnets" is held by images related to human life in the steppe - a field, a pond, a bee. The opposition between steppe and field is not clear, but it is evident. The steppe appears untouched, purely natural, while the field is cultivated by people, closer to Ukrainian villages. In the sonnets by Yar Slavutych, the conceptuality of natural elements is clearly traced: the heavenly bodies, the earth, and water. The poet widely and skillfully uses many tropes (metaphors, metonymies, litanies, etc.). The image that combines the power of the elements of nature and at the same time is purely human is the image of a man - a man of work. One of the key images-symbols associated with the life of people in the steppe in the poetry of Yar Slavutych is the image of the path. The distinctive means of the poetics of the "Kherson Sonnets" are the following: major language style, classical metrics, musical phrasing, metaphor, hyperbole, instantaneous perception of what is seen, and wide-ranging thought.
Peculiarities of Landscape Lyrics by Yar Slavutych (Based on the Cycle «Kherson Sonnets»)
І. Ляшенко: ORCID 0000-0002-7816-2339
Keywords: пейзажна лірика; образ степу; мала батьківщина; художні тропи; жанр сонета; landscape poetry; image of the steppe; small motherland; artistic tropes; sonnet genre; КФУ; HUMANITIES and RELIGION; HUMANITIES and RELIGION::Aesthetic subjects::Literature